Spatial Mapping And Analysis Of The Harvest Time Determination Of Paddy (Oryza sativa L.) Using The Thermal Unit Of The Southeast Minahasa Regency: - Rombe, Nadia Jovanka; Rogi, Johannes E. X; Paulus, Jeanne M.; Paat, Frangky J. (Sam Ratulangi University, 2024)
Climate change since 2019 has had a significant impact on paddy plant growth, presenting new challenges in optimizing food production. An effective approach in determining the harvest timing is the Thermal Unit Concept, which takes into account the accumulation of daily temperature during the rice plant's growth. Spatial mapping using Geographic Information System (GIS) is employed to analyze land conditions and heat requirements in paddy cultivation. The mapping results are valuable for planning, cultivation, governmental policy-making, and dissemination to farmers. This research was conducted from August to November in the Rasi Village, Southeast Minahasa, North Sulawesi Province. Data collection involved observing the phenology of rice plants, recording coordinates of planting and harvesting locations, and digitizing Landsat images using SAS Planet and ArcGIS 10.8. Daily temperature analysis was carried out to obtain thermal unit values. The digitized map revealed the paddy field area in Southeast Minahasa Regency to be 3,002.621 hectares, distributed across all sub-districts. The sub-district with the largest paddy field area was North Tombatu, covering 521.362 hectares, while South Touluaan had the smallest area at 32.142 hectares. The Thermal Unit analysis indicated that Southeast Minahasa Regency/Rasi requires 1,285.11 thermal units, with varying heat requirements in each growth phase. During the seeding-planting phase, paddy plants need 292.79 °C, seedling-transplanting 460.04 °C, seedling-anthesis, and heading 217.57 °C, and during the anthesis and heading-harvest phase, paddy plants require 314.71 °C. Keywords: Spatial Mapping, Thermal Unit, Paddy (Oryza sativa L.) Abstrak Perubahan iklim yang terjadi sejak tahun 2019 telah memberikan dampak signifikan pada pertumbuhan tanaman padi, menghadirkan tantangan baru dalam mengoptimalkan produksi pangan. Pendekatan efektif dalam menentukan waktu panen adalah Konsep Thermal Unit, yang memperhitungkan akumulasi suhu harian selama pertumbuhan tanaman padi. Pemetaan spasial menggunakan Sistem Informasi Geografis digunakan untuk menganalisis kondisi lahan dan kebutuhan panas dalam pertanian padi. Hasil pemetaan ini berguna untuk perencanaan, pembudidayaan, serta pengambilan kebijakan pemerintah dan disosialisasikan kepada petani. Penelitian ini dilaksanakan pada bulan Agustus – November di Desa Rasi, Minahasa Tenggara Provinsi Sulawesi Utara. Pengumpulan data penelitian dilakukan dengan pengamatan fenologi tanaman padi, mengambil titik koordinat lokasi dan waktu/tanggal semai-panen tanaman padi, kemudian dilakukan digitasi Citra Landsat, Sas Planet ArcGIS 10.8 dan menganalisis suhu harian untuk mendapatkan nilai thermal unit. Hasil digitasi peta mendapatkan luas sawah di kabupaten Minahasa Tenggara sebesar 3.002,621 ha yang tersebar diseluruh kecamatan yang ada di Minahasa Tenggara, Kecamatan yang memiliki luas lahan sawah terbesar yaitu kecamatan Tombatu Utara sebesar 521,362 ha, sedangkan untuk kecamatan dengan luas lahan terkecil yaitu Touluaan Selatan sebesar 32,142 ha. Hasil analisis Thermal Unit menunjukan bahwa kabupaten Minahasa Tenggara / Rasi : 1.285,11 d0C, dengan jumlah kebutuhan panas yang berbeda-beda disetiap fasenya. Pada fase semai – tanam, tanaman padi memerlukan 292,79 d0C, tanam-anakan 460,04 d0C, anakan – anthesis dan bunting 217,57 d0C, serta pada fase anthesis dan bunting – panen tanaman padi memerlukan 314,71 d0C. Kata Kunci : Pemetaan Spasial, Thermal Unit, Padi (Oryza sativa L).